Preparation method and application of anti-icing, self-cleaning and radiation refrigeration multifunctional coating

By using a multifunctional coating of modified TiO2 and α-phosphogypsum in superhydrophobic radiation cooling coatings, combined with a cross-linking network of epoxy resin and polyethyleneimine, it solves the difficulty of existing coatings to take into account both anti-icing, cooling and self-containing. The problem of cleaning performance achieves efficient radiation refrigeration and excellent outdoor durability.

CN119432202AActive Publication Date: 2025-02-14CHINA THREE GORGES UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411374030.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-14
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The existing superhydrophobic radiation cooling coatings are difficult to take into account anti-icing, cooling and self-cleaning properties, and they are not durable outdoors.

Method used

Using a multifunctional coating based on E51-PEI-PDMS-SiO2-TiO2-α-phosphogypsum, a micro-nano double-rough structure is formed by modifying TiO2 and α-phosphogypsum, combining cross-linking of epoxy resin and polyethyleneimine network, increasing the mechanical properties and connection strength of the coating.

Benefits of technology

The coating is versatile in anti-ice, self-cleaning and radiation refrigeration performance, and significantly improves outdoor durability and mechanical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432202A_ABST
    Figure CN119432202A_ABST
Patent Text Reader

Abstract

The invention discloses a multifunctional coating with anti-icing, radiation refrigeration and self-cleaning effects and a preparation method thereof. The coating mainly comprises SiO2 nanoparticles, TiO2 nanoparticles, alpha-ardealite, epoxy resin (E51), polyethyleneimine (PEI), polydimethylsiloxane (PDMS) and a curing agent thereof, slurry is prepared by adopting a simple blending method, and film coating is performed by adopting a scraper method, so that the multifunctional coating with anti-icing, radiation refrigeration and self-cleaning effects can be prepared. No fluorine-containing reagent is used in the preparation of the coating, the coating is environment-friendly, and the surface of the coating can be prevented from being polluted by the outside due to the self-cleaning characteristic of the coating, so that stable anti-icing and radiation refrigeration performance is kept. In addition, the composite coating shows good durability in a mechanical wear test, a chemical stability test and an outdoor weather test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional coatings, and in particular relates to an anti-icing, self-cleaning, and radiation cooling multifunctional coating and a preparation method thereof. Background Art

[0002] As the rapid growth of energy consumption has raised concerns about energy depletion and severe environmental impacts, it is of great significance to develop cheap and efficient cooling coatings and refrigeration technologies that can alleviate global energy demand and climate impacts. Radiative cooling (RC) is a new method for saving energy and reducing ambient temperature. It has the characteristics of no energy consumption. It strongly reflects sunlight in the visible near-infrared band (0.3-2.5μm) and sends infrared heat to the universe in the atmospheric transparent window (8-13μm). Since cooling coatings are usually applied to outdoor power equipment, roofs and other building surfaces, when they are exposed to the external use environment for a long time, complex environments such as rain scouring, dust accumulation, and sunlight exposure will destroy the optical properties of the material, reduce its reflectivity and thus reduce the cooling effect. Especially under extreme cold conditions in winter, ice coating and ice melting on the surface will seriously damage the microstructure of the coating, causing its radiative cooling effect to decay sharply. Therefore, the development of coatings with multiple functions of superhydrophobicity, anti-icing and radiative cooling is crucial for the outdoor durability of radiative cooling coatings. However, there are few reports on such multifunctional composite materials. Existing super-hydrophobic materials are mainly achieved by constructing a micro-nano double rough structure with low surface energy. The most common method is to use SiO2 as the main particle to construct a super-hydrophobic surface. The radiative cooling coating requires a material with high reflectivity and high emissivity to form a mesh structure to achieve the best radiative cooling effect.

[0003] Although adding radiative cooling materials with high emissivity or high reflectivity, such as TiO2, ZnO, MgTiO3, SrTiO3 and BaTiO3, to super-hydrophobic coatings can improve the cooling performance of the coating to a certain extent, the effect is still not ideal, mainly because it is difficult for such materials to have both high emissivity and high reflectivity. At the same time, these material additives usually lead to a decrease in hydrophobic performance. Summary of the invention

[0004] In order to solve the technical difficulties of existing super-hydrophobic radiant cooling coatings, the present invention proposes a super-hydrophobic, anti-icing and radiant cooling multifunctional coating based on E51-PEI-PDMS-SiO2-TiO2-α-phosphogypsum and a preparation method thereof, an anti-icing, self-cleaning, radiant cooling multifunctional coating and a preparation method thereof, which solve the problem that existing coatings are difficult to take into account anti-icing, cooling, self-cleaning and excellent outdoor durability.

[0005] The technical solution of the present invention: TiO2 was modified using NaOH, Na2SO4, KH570 and α-phosphogypsum to improve its hydrophobicity and reflectivity. Superhydrophobic SiO2 nanoparticles, TiO2 nanoparticles and modified α-phosphogypsum were then used as the main fillers. Epoxy resin (E51) and polyethyleneimine (PEI) were added. PEI has highly reactive primary and secondary amines, which can easily react with the epoxy groups in E51 to form a stable cross-linked network, thereby improving the connection strength within the coating and between the coating and the substrate. Finally, polydimethylsiloxane (PDMS) and its curing agent were added to cross-link and cure the coating after the solvent evaporated, further improving its mechanical properties.

[0006] An anti-icing, self-cleaning, radiation cooling multifunctional coating and a preparation method thereof, comprising the following steps: Step 1: Add α-phosphogypsum, NaOH and Na2SO4 to deionized water, stir, add TiO2 nanoparticles, continue stirring, filter, microwave, wash and dry to obtain α-phosphogypsum-TiO2 mixed powder; Step 2: Anhydrous ethanol, deionized water and KH570 are mixed and stirred, and after heating, the mixed powder obtained in step 1 is added, and the mixture is continuously stirred under heating and then filtered, washed, dried, ground and sieved to obtain modified TiO2 nanoparticles; Step 3: adding super-hydrophobic SiO2 nanoparticles and modified TiO2 nanoparticles into an ethyl acetate dispersion solvent, and obtaining a mixed suspension of SiO2 and modified TiO2 after ultrasonic dispersion; Step 4: Add E51 and PEI to the mixed suspension obtained in step 3 and stir to obtain a mixed solution; Step 5: Add PDMS and its curing agent to the mixed solution obtained in step 4 and stir to obtain a super hydrophobic coating; Step 6: The coating obtained in step 5 is coated on the substrate by a scraper method, and after solvent drying, an anti-icing, radiation cooling, and self-cleaning multifunctional coating of SiO2, TiO2, and hydrophobically modified α-phosphogypsum is obtained.

[0007] In the step 1, the mass ratio is TiO2: α-phosphogypsum: NaOH: Na2SO4 = 0.3~3: 3~9: 1~5: 0.2~2; the microwave power is 60W~150W, and the microwave irradiation time is 2~8min.

[0008] Further, as a preferred embodiment, in step 1, the mass ratio of TiO2: α-phosphogypsum: NaOH: Na2SO4 is 1:6: 3: 0.5; the magnetic stirring speed is 800 r / min; The microwave power was 100 W and the microwave irradiation time was 3-5 min.

[0009] In step 2, the mass concentration of KH570 is 0.025-1 g / mL, and the mass ratio is KH570: modified TiO2 = 0.2~1: 2~12, preferably 0.53: 6; the stirring temperature is 50°C~80°C, preferably 60°C.

[0010] In step 3, the particle size of the super-hydrophobic SiO2 nanoparticles is 7-40 nm, and the specific surface area is 100-200 m 2 / g; the particle size of modified TiO2 is 90-120 mesh, the total mass concentration of the suspension of superhydrophobic SiO2 nanoparticles and modified TiO2 is 0.053-0.1 g / mL, and in terms of mass ratio, superhydrophobic SiO2 nanoparticles: modified TiO2 = 1:0.1~3:2.

[0011] In the step 4, the mass ratio of E51:PEI is 3-5:1, and the stirring temperature is 65-75°C.

[0012] In the step 5, the PDMS mass concentration in the PDMS mixed solution is 0.013-0.1 g / mL, and after stirring for 30 min-1 h, it is cured at 120-140 ° C for 2 to 3 h.

[0013] In step 6, the weight proportion of the coating includes: 30 to 50 parts of super-hydrophobic SiO2 nanoparticles, 5 to 50 parts of modified TiO2 nanoparticles, 20-30 parts of E51, 10-15 parts of PEI, and 15-20 parts of PDMS, and the mass ratio of PDMS to curing agent is 10-20:1.

[0014] In a preferred embodiment, the coating comprises by weight: 30 to 50 parts of super-hydrophobic SiO2 nanoparticles, 5 to 50 parts of modified TiO2 nanoparticles, 30 parts of E51, 10 parts of PEI, and 20 parts of PDMS, and the mass ratio of PDMS to curing agent is 10:1.

[0015] In step 6, the scraping film thickness of the scraping method is 100-300 μm (preferably 200 μm), and the material of the substrate includes any one of a glass sheet, an aluminum sheet, a copper sheet, and a carbon steel sheet.

[0016] The coating obtained by the preparation method of the anti-icing, radiation cooling and self-cleaning multifunctional coating is used in materials with any one or more properties of anti-icing, radiation cooling and self-cleaning.

[0017] Beneficial effects of the present invention: 1. Multifunctionality. The multifunctional coating of the present invention has anti-icing, self-cleaning, and radiation cooling properties, and has excellent mechanical stability, aging resistance, and acid and alkali resistance.

[0018] 2. Good durability. In outdoor application scenarios, the multifunctional coating samples were exposed for two months, and the performance of the coating did not show obvious attenuation.

[0019] 3. The multifunctional coating of the present invention is difficult for hydrophilic pollutants to adhere to, and can be applied to various fields such as self-cleaning, anti-icing, deicing, and hydrophobicity.

[0020] 4. The multifunctional coating of the present invention does not contain toxic reagents and is environmentally friendly.

[0021] 5. The present invention utilizes α-phosphogypsum to modify TiO2. On the one hand, α-phosphogypsum particles and TiO2 nanoparticles are used to form a micro-nano double rough structure, and KH570 is used to perform low surface energy modification on it to make it super hydrophobic. On the other hand, phosphogypsum and TiO2 nanoparticles are hybridized to significantly improve their reflectivity, thereby significantly improving the radiation cooling effect of the coating.

[0022] 6. The present invention utilizes epoxy resin E51 and polyethyleneimine PEI to cross-link each other, which plays a connecting role between the two nanoparticles and the substrate. The addition of PDMS makes the coating strong and durable, and the coating has good mechanical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The water drop contact angle test results of the coatings in Examples 1, 2, 3, 4, 5, 6, and 7 are shown.

[0024] Figure 2 The graphs are the test results of water droplet rolling angle of the coatings in Examples 1, 2, 3, 4, 5, 6, and 7.

[0025] Figure 3 These are experimental diagrams of the coatings on the aluminum substrates of Examples 2, 3, 4, 5, and 6 in ice melting tests.

[0026] Figure 4 This is a graph showing the ice-shedding force test results of the coating on the aluminum substrate of Examples 2, 3, 4, 5, and 6 after being detached by external force after freezing of different volumes of deionized water.

[0027] Figure 5 The graphs show the test results of the water drop contact angle and rolling angle of the coating on the aluminum substrate of Examples 2, 3, 4, 5, and 6 after multiple freezing and thawing cycles.

[0028] Figure 6 This is a graph showing the radiation cooling test results of the coating of Example 1 under direct sunlight.

[0029] Figure 7This is a graph showing the temperature difference results of the radiation cooling test of the coating in Example 1 under direct sunlight.

[0030] Figure 8 The following are the test results of the radiation cooling of the coatings of Examples 2, 3, 4, 5 and 6 under direct sunlight.

[0031] Fig. 9 This is a graph showing the temperature difference results of the radiation cooling test of the coatings of Examples 2, 3, 4, 5, and 6 under direct sunlight.

[0032] Fig.10 The graphs show the test results of the water drop contact angle and the rolling angle of the coatings in Examples 2, 3, 4, 5, and 6 in the 20 g gravel 40 cm height cyclic impact test.

[0033] Fig.11 The graphs show the test results of water drop contact angle and rolling angle of the coating in Examples 2, 3, 4, 5 and 6 in the cyclic friction test on 1000-grit sandpaper with a load of 50 g.

[0034] Fig.12 The graphs show the test results of water drop contact angle and rolling angle of the coatings in Examples 2, 3, 4, 5, and 6 when immersed in a pH = 2 HCl solution for 10 days.

[0035] Fig.13 The test results of water drop contact angle and rolling angle of the coating in Examples 2, 3, 4, 5, and 6 were obtained by immersing the coating in a NaOH solution with a pH of 10 for 10 days.

[0036] Fig.14 The graphs show the test results of water drop contact angle and rolling angle of the coatings in Examples 2, 3, 4, 5 and 6 after being placed outdoors for two months. DETAILED DESCRIPTION

[0037] In order to further understand the content and features of the present invention, embodiments of the present invention are given below. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0038] The experimental methods in the following examples are conventional methods unless otherwise specified.

[0039] Example 1 A method for preparing an anti-icing, self-cleaning and radiative cooling multifunctional coating comprises the following steps: Step 1: At room temperature, 1 g TiO2 nanoparticles, 6 g α-phosphogypsum, 3 g NaOH and 0.5 g Na2SO4 were added to 30 g deionized water, stirred for 30 minutes and filtered to obtain a filter cake. The filter cake was microwaved at 100 W for 1 min, washed thoroughly (first washed with deionized water 3 times, then washed with anhydrous ethanol 3 times), and dried at 60 ° C for 12 h to obtain a TiO2-α-phosphogypsum mixed powder.

[0040] Step 2: Add 20 mL of anhydrous ethanol, 1.25 mL of deionized water and 0.53 g of KH570 to a beaker. Stir and heat to 60 °C, then add 6 g of the mixed powder obtained in step 1, continue stirring and heating for 2.5 h, filter, wash with anhydrous ethanol three times, dry at 60 °C for 12 h, grind, and sieve through a 90-mesh sieve to obtain modified TiO2 nanoparticles.

[0041] Step 3: Particle size 7 - 40 nm, specific surface area 100 m 2 0.4 g / g superhydrophobic SiO2 nanoparticles and 0.3 g modified TiO2 nanoparticles obtained in step 2 are added into 15 mL ethyl acetate dispersion solvent, and magnetically stirred at 700-800 r / min for 15-20 min to obtain a mixed suspension of SiO2 and modified TiO2 nanoparticles; Step 4: Add 0.3 g E51 and 0.1 g PEI to the mixed suspension obtained in step 3, and stir magnetically for 2 h to obtain a mixed solution; Step 5: Add 0.2 g PDMS and 0.02 g curing agent to the mixed solution obtained in step 4 and stir magnetically for 1 h to obtain a super hydrophobic coating; Step 6: Place the aluminum substrate in a plasma cleaner for 1 min, scrape the film with a scraper of 200 μm in height at room temperature, and dry it in a 120 °C oven for 2 h to obtain a SiO2 and modified TiO2 anti-icing and radiation cooling multifunctional super-hydrophobic coating.

[0042] Through the above steps, the water contact angle of the coating prepared on the aluminum substrate reached a maximum of 156.5° ( Figure 1 ), the roll angle is 5° ( Figure 2 ). Compared with the ambient temperature, the temperature difference ΔT on the sample surface of this embodiment can reach up to 20°C, and the average temperature drop is 16.3°C ( Figure 6 , Figure 7 ), has excellent cooling effect.

[0043] Example 2 Compared with Example 1, α-phosphogypsum is not added in step 1, and the rest is the same as Example 1.

[0044] After testing, the water contact angle of the coating prepared on the aluminum substrate reached up to 157.25° ( Figure 1 ), the roll angle is 2.25° ( Figure 2 ). The aluminum substrate and the coating prepared in this example were placed on a cooling table, and 20 μL of deionized water was dripped on each of them. After the cooling table was started, the freezing process was as follows ( Figure 3 ): Water droplets on bare aluminum began to freeze at 239 s, and the water droplets on the coating were completely frozen after 282 s; water droplets on the sample of this embodiment began to freeze at 1158 s, and were completely frozen after 1223 s. The freezing delay time was about 4.5 times that of the aluminum substrate, which proved that the coating in this embodiment could significantly prolong the freezing time of water droplets compared with the aluminum substrate and had an excellent anti-icing effect.

[0045] The forces required to detach the deionized water with a volume of 40, 60, 80, and 100 μL after freezing on the sample surface in this embodiment are 5.25, 7.015, 10.411, and 13.992 N, respectively. Figure 4 ), the average de-icing force is 9.167 N. Compared with the aluminum substrate (average de-icing force is 16.297 N), the sample of this embodiment can reduce the de-icing force by nearly half, proving that the sample of this embodiment is easier to remove ice from the surface. After 27 ice formation and ice melting cycles at the same marked position, the water contact angle of the coating in this embodiment is still maintained above 150°, and the water rolling angle is below 10° ( Figure 5 ), which proves that it has good durability in anti-icing scenarios.

[0046] Compared with the ambient temperature, the temperature difference ΔT on the sample surface of this embodiment can reach up to 17.3 ℃, and the average temperature drop is 13.6 ℃ ( Figure 8 , Fig. 9 ), the cooling effect is not as good as that in Example 1, indicating that when α-phosphogypsum is not added, the cooling effect of the coating is significantly reduced.

[0047] The sample of this embodiment has been subjected to 26 cycles ( Fig.10 ), and 45 cycles of cyclic abrasion test on 1000 grit sandpaper with a load of 50 g ( Fig.11 ) still maintains a superhydrophobic state. The sample is immersed in a pH = 2 HCl solution ( Fig.12 ), pH = 10 NaOH solution ( Fig.13 ) for 10 days and remained super hydrophobic. The samples were directly exposed to outdoor natural conditions for 2 months. During the entire test, WCA remained above 150° and SA was less than 10° ( Fig.14 ), the superhydrophobicity of the sample is basically maintained, indicating that the sample is not damaged by rain or other environmental factors and has good weather resistance and long-term stability.

[0048] Example 3 Compared with Example 1, Step 1 and Step 2 are omitted, and only 0.5 g of SiO2 nanoparticles are added in Step 3, and the rest is the same as Example 1. The water contact angle of the tested coating is 156.5° ( Figure 1 ), roll angle 2.5° ( Figure 2 ). The coating prepared in this example was placed in the freezing experiment of Example 1, and the freezing process was observed as follows: the water droplets on the coating began to freeze at 1009 s, and the water droplets on the coating were completely frozen after 1072 s ( Figure 3 ).

[0049] The forces required to detach the deionized water with a volume of 40, 60, 80, and 100 μL after freezing on the sample surface in this embodiment are 4.979, 8.572, 11.981, and 14.246 N, respectively. Figure 4 ), the average deicing force is 9.945 N. After 27 ice-melting cycles at the same marked position, the water contact angle of the coating in this embodiment is maintained above 150° and the water rolling angle is below 10° ( Figure 5 ).

[0050] Compared with the ambient temperature, the sample surface temperature difference ΔT of the sample in this embodiment can reach up to 16.9 ℃, and the average temperature drop is 11.4 ℃ ( Figure 8 , Fig. 9 ), the cooling effect is not as good as that in Example 1, indicating that when modified TiO2 is not added, the cooling effect of the coating is significantly reduced.

[0051] The sample of this embodiment has been subjected to 22 cycles ( Fig.10 ), and 32 cycles of cyclic abrasion test on 1000 grit sandpaper with a load of 50 g ( Fig.11 ) still maintains a superhydrophobic state. The sample was immersed in a pH = 2 HCl solution ( Fig.12 ), pH = 10 NaOH solution ( Fig.13 ) for 10 days and remained super hydrophobic. The samples were directly exposed to outdoor natural conditions for 2 months. During the entire test, WCA remained above 150° and SA was less than 10° ( Fig.14 ).

[0052] Example 4 Compared with Example 1, α-phosphogypsum is not added in step 1, and the amount of TiO2 nanoparticles added is changed to 0.2 g, and the rest is the same as Example 1. The water contact angle of the tested coating can reach 158.25° ( Figure 1 ), roll angle 1.25° ( Figure 2). The coating prepared in this example was placed in the freezing experiment of Example 1, and the freezing process was observed as follows: the water droplets on the coating began to freeze at 1213 s, and the water droplets on the coating were completely frozen after 1292 s ( Figure 3 ).

[0053] The forces required to detach the deionized water with a volume of 40, 60, 80, and 100 μL after freezing on the sample surface in this embodiment are 3.887, 7.084, 11.314, and 13.056 N, respectively. Figure 4 ), the average deicing force is 8.835 N. After 27 ice-melting cycles at the same marked position, the water contact angle of the coating in this embodiment is maintained above 150° and the water rolling angle is below 10° ( Figure 5 ).

[0054] Compared with the ambient temperature, the sample surface temperature difference ΔT of the sample in this embodiment can reach up to 16.5 ℃, and the average temperature drop is 12.3 ℃ ( Figure 8 , Fig. 9 ), indicating that the cooling effect of the coating is significantly reduced when α-phosphogypsum is not added.

[0055] The sample was subjected to 24 cycles of 20 g gravel 40 cm height cyclic impact test ( Fig.10 ), and 41 cycles of cyclic abrasion testing on 1000 grit sandpaper with a load of 50 g ( Fig.11 ) still maintains a superhydrophobic state. The sample is immersed in a pH = 2 HCl solution ( Fig.12 ), pH = 10 NaOH solution ( Fig.13 ) for 10 days and remained super hydrophobic. The samples were directly exposed to outdoor natural conditions for 2 months. During the entire test, WCA remained above 150° and SA was greater than 10° ( Fig.14 ).

[0056] Example 5 Compared with Example 1, α-phosphogypsum is not added in step 1, the amount of TiO2 nanoparticles is changed to 0.5 g, the amount of SiO2 nanoparticles in step 3 is changed to 0.35 g, and the rest is the same as Example 1. The water contact angle of the coating is tested to be 155.5° ( Figure 1 ), rolling angle 3.25° ( Figure 2 ). The coating prepared in this example was placed in the freezing experiment of Example 1, and the freezing process was observed as follows: the water droplets on the coating began to freeze at 946 s, and the water droplets on the coating were completely frozen after 1012 s ( Figure 3 ).

[0057] The forces required to detach the deionized water with a volume of 40, 60, 80, and 100 μL after freezing on the sample surface in this embodiment are 6.640, 8.763, 11.232, and 15.175 N, respectively. Figure 4 ), the average deicing force is 10.453 N. After 27 ice-melting cycles at the same marked position, the water contact angle of the coating in this embodiment is maintained above 150° and the water rolling angle is below 10° ( Figure 5 ).

[0058] Compared with the ambient temperature, the sample surface temperature difference ΔT of the sample in this embodiment can reach up to 15.5 ℃, and the average temperature drop is 10 ℃ ( Figure 8 , Fig. 9 ), indicating that the cooling effect of the coating is significantly reduced when α-phosphogypsum is not added.

[0059] The sample of this embodiment has been subjected to 19 cycles ( Fig.10 ), and 35 cycles of cyclic abrasion test on 1000 grit sandpaper with a load of 50 g ( Fig.11 ) still maintains a superhydrophobic state, and its mechanical properties are poorer than those of the sample in Example 1. The sample is immersed in a pH = 2 HCl solution ( Fig.12 ), pH = 10 NaOH solution ( Fig.13 ) for 10 days with a rolling angle of more than 10°. The samples were directly exposed to outdoor natural conditions for 2 months. During the entire test process, the WCA remained above 150° and the SA was slightly higher than 10° ( Fig.14 ).

[0060] Example 6 Compared with Example 1, α-phosphogypsum was not added in step 1, 0.3 g of SiO2 nanoparticles and 0.67 g of TiO2 nanoparticles were added in step 3, and the rest was the same as Example 1. The water contact angle of the coating was tested to be 154.75° ( Figure 1 ), the roll angle is 4° ( Figure 2 ). The coating prepared in this example was placed in the freezing experiment of Example 1, and the freezing process was observed as follows: the water droplets on the coating began to freeze at 823 s, and the water droplets on the coating were completely frozen after 882 s ( Figure 3 ).

[0061] The forces required to detach the deionized water with a volume of 40, 60, 80, and 100 μL after freezing on the sample surface in this embodiment are 6.897, 9.592, 13.201, and 15.943 N, respectively. Figure 4 ), the average deicing force is 11.408 N, which is greater than that of the sample in Example 1. After 27 cycles of ice formation and thawing at the same marked position, the water rolling angle of the coating in this embodiment is about 15° ( Figure 5 ).

[0062] Compared with the ambient temperature, the sample surface temperature difference ΔT of the sample in this embodiment can reach up to 14 ℃, and the average temperature drop is 9.6 ℃ ( Figure 8 , Fig. 9 ), the cooling effect is poor compared with the sample in Example 1.

[0063] The sample of this embodiment has been subjected to 15 cycles ( Fig.10 ), and 25 cycles of cyclic abrasion test on 1000 grit sandpaper with a load of 50 g ( Fig.11 ) maintains a superhydrophobic state, and its mechanical properties are poorer than those of the sample in Example 1. The sample is immersed in a pH = 2 HCl solution ( Fig.12 ), pH = 10 NaOH solution ( Fig.13 ) for 10 days with a rolling angle of more than 10°. The samples were directly exposed to outdoor natural conditions for 2 months. During the entire test process, the WCA was maintained above 150° and the SA was greater than 10° ( Fig.14 ), the super-hydrophobicity of the sample in this embodiment is lost, and the acid and alkali resistance and weather resistance are poorer than those of the sample in Example 1.

[0064] Example 7 Compared with Example 1, step 1 and step 2 are omitted, and only 0.5 g of TiO2 nanoparticles are added in step 3, and the rest is the same as Example 1. The test results show that the water contact angle of the coating is 139.25° and the rolling angle is 43°, indicating that excessive use of nano-TiO2 will cause the coating to lose its superhydrophobicity.

[0065] Example 8 Compared with Example 1, the amount of NaOH added in step 1 is 4g, and the rest is the same as Example 1. In the hydrophobicity test, the water contact angle of the coating is 157.3°, and the rolling angle is 2.8°. In the cooling performance test, the temperature difference ΔT on the surface of the sample of this embodiment compared with the ambient temperature can reach up to 19.5°C, and the average temperature reduction is 16.0°C, which has an excellent cooling effect.

[0066] Example 9 Compared with Example 1, the amount of Na2SO4 added in step 1 is 0.4g, and the rest is the same as Example 1. In the hydrophobicity test, the water contact angle of the coating is 155.3°, and the rolling angle is 4.5°. In the cooling performance test, the temperature difference ΔT on the surface of the sample of this embodiment compared with the ambient temperature can reach up to 19.5°C, and the average temperature drop is 16.4°C, which has an excellent cooling effect.

[0067] Example 10 Compared with Example 1, the amount of α-phosphogypsum added in step 1 is 5g, and the rest is the same as Example 1. In the hydrophobicity test, the water contact angle of the coating is 156.8°, and the rolling angle is 3.7°. In the cooling performance test, the temperature difference ΔT on the surface of the sample of this embodiment compared with the ambient temperature can reach up to 19.6°C, and the average temperature reduction is 16.1°C, which has an excellent cooling effect.

Claims

1. A method for preparing an anti-icing, self-cleaning, and radiation cooling multifunctional coating, characterized in that: The following steps are involved: Step 1: Add α-phosphogypsum, NaOH and Na2SO4 to deionized water, stir, add TiO2 nanoparticles, continue stirring, filter, microwave, wash and dry to obtain α-phosphogypsum-TiO2 mixed powder; Step 2: Anhydrous ethanol, deionized water and KH570 are mixed and stirred, and after heating, the mixed powder obtained in step 1 is added, and the mixture is continuously stirred under heating and then filtered, washed, dried, ground and sieved to obtain modified TiO2 nanoparticles; Step 3: adding super-hydrophobic SiO2 nanoparticles and modified TiO2 nanoparticles into an ethyl acetate dispersion solvent, and obtaining a mixed suspension of SiO2 and modified TiO2 after ultrasonic dispersion; Step 4: Add E51 and PEI to the mixed suspension obtained in step 3 and stir to obtain a mixed solution; Step 5: Add PDMS and its curing agent to the mixed solution obtained in step 4 and stir to obtain a super hydrophobic coating; Step 6: The coating obtained in step 5 is coated on the substrate by a scraper method, and after solvent drying, an anti-icing, radiation cooling, and self-cleaning multifunctional coating of SiO2, TiO2, and hydrophobically modified α-phosphogypsum is obtained.

2. The method for preparing the anti-icing, self-cleaning and radiation cooling multifunctional coating according to claim 1, characterized in that: In the step 1, the mass ratio of TiO2: α-phosphogypsum: NaOH: Na2SO4 is 0.3~3: 3~9: 1~5: 0.2~2; the magnetic stirring speed is 800 ~ 900 r / min; The microwave power is 60 W ~150 W, and the microwave irradiation time is 2 ~ 8 min.

3. The method for preparing the anti-icing, self-cleaning and radiation cooling multifunctional coating according to claim 2, characterized in that: In the step 1, the mass ratio is TiO2: α-phosphogypsum: NaOH: Na2SO4 = 1:6: 3: 0.5; the magnetic stirring speed is 800 r / min; The microwave power was 100 W and the microwave irradiation time was 3-5 min.

4. The method for preparing the anti-icing, self-cleaning and radiation cooling multifunctional coating according to claim 1, characterized in that: In the step 2, the mass concentration of KH570 is 0.025-0.1 g / mL, and the mass ratio is KH570: modified TiO2 = 0.2~1: 2~12, preferably 0.53: 6; the stirring temperature is 50°C~80°C, preferably 60°C.

5. The method for preparing the anti-icing, self-cleaning and radiation cooling multifunctional coating according to claim 1, characterized in that: In step 3, the particle size of the super-hydrophobic SiO2 nanoparticles is 7-40 nm, and the specific surface area is 100-200 m 2 / g; the particle size of modified TiO2 is 90-120 mesh, the total mass concentration of the suspension of superhydrophobic SiO2 nanoparticles and modified TiO2 is 0.053-0.1g / mL, and in terms of mass ratio, superhydrophobic SiO2 nanoparticles: modified TiO2 = 1:0.1~3:

2.

6. The method for preparing the anti-icing, self-cleaning, radiation cooling multifunctional coating according to claim 1, characterized in that: In the step 4, the mass ratio of E51:PEI is 3-5:1, and the stirring temperature is 65-75°C.

7. The method for preparing the anti-icing, self-cleaning and radiation cooling multifunctional coating according to claim 1, characterized in that: In the step 5, the PDMS mass concentration in the PDMS mixed solution is 0.013-0.1 g / mL, and after stirring for 30 min-1 h, it is cured at 120-140 ° C for 2 to 3 h.

8. The method for preparing the anti-icing, self-cleaning, radiation cooling multifunctional coating according to claim 1, characterized in that: In step 6, the weight proportion of the coating includes: 30 to 50 parts of super-hydrophobic SiO2 nanoparticles, 5 to 50 parts of modified TiO2 nanoparticles, 20-30 parts of E51, 10-15 parts of PEI, and 15-20 parts of PDMS, and the mass ratio of PDMS to curing agent is 10-20:

1.

9. The method for preparing the anti-icing, self-cleaning and radiation cooling multifunctional coating according to claim 1, characterized in that: In step 6, the scraping film thickness of the scraping method is 100-300 μm, and the material of the substrate includes any one of a glass sheet, an aluminum sheet, a copper sheet, and a carbon steel sheet.

10. Application of the coating obtained by the preparation method of the multifunctional coating according to any one of claims 1 to 9 in materials having any one or more properties of anti-icing, radiation cooling, and self-cleaning.

Citation Information

Patent Citations

  • Composite super-hydrophobic radiation refrigeration coating material and preparation method thereof

    CN114106691A

  • Preparation method of high-robustness super-hydrophobic anti-icing fabric

    CN115787306A

  • Preparation method of hydrophobic self-cleaning coating hybridized with nano silicon dioxide on surface of beta-hemihydrate phosphogypsum

    CN116285670A

  • Radiative cooling devices using ceramic nano-particles mixture

    KR102230348B1

  • Polymeric composition with Anti-icing and self-cleaning properties

    US20190233675A1